Experience Of Obtaining Fry Cyprinid Fish in Drainage Water In Bukhara Region - Usmanova D.B; Nosirov О.T; Toshova N.R; Yuldashev М.А (Genius Publishing Group, 2023)
Great attention is paid to the rational use of all available water resources in Uzbekistan. Currently, we practically have a managed unified irrigation system, which was created as a result of large-scale irrigation construction since the second half of the twentieth century. The flow of all major rivers in the Aral Sea basin was fully regulated for these purposes. This could not but affect the country's fish resources. In turn, the fully privatized fisheries sector of Uzbekistan has strategically gone in the right direction - the development of various approaches and aquaculture systems on available water resources. The characteristics of water resources for the development of a particular area of aquaculture must be taken into account. Thus, in irrigation systems, water accumulation in the autumn-spring period is carried out in reservoirs, then the water flow is redistributed in time and in the directions of water flows for economic needs. Naturally, it is better to locate reservoirs in mountainous and foothill zones. It is in the reservoirs and irrigation canal system that the water is clean and fresh
Keywords: canal; economic; reservoirs; zones